2015
DOI: 10.1016/j.ydbio.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed meibomian gland and tarsal plate morphogenesis by excess TGFα in eyelid stroma

Abstract: Transforming growth factor alpha (TGFα) belongs to the epidermal growth factor (EGF) family and is known to play an important role during eyelid morphogenesis. In this study, we showed that ectopic expression of TGFα in the stroma of Kera-rtTA/tet-O-TGFα bitransgenic mice results in precocious eye opening, abnormal morphogenesis of the meibomian gland, tendon and tarsal plate malformation and epithelium hyperplasia. TGFα did not change proliferation and differentiation of meibocytes, but promoted proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…34 The double transgenic mouse KR/TGF-α was created to express TGF-α in corneal stromal cells with Dox administration. The eyes of Dox-induced KR/TGF-α mice looked normal and transparent 20 ; no dramatic phenotypes were observed. This inconsistent consequence of ectopic expression of TGF-α in cornea of these two mouse strains is probably owing to different expression levels of TGF-α in their corneal stroma, which suggested that lower TGF-α level was produced in KR/TGF-α mouse strain.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…34 The double transgenic mouse KR/TGF-α was created to express TGF-α in corneal stromal cells with Dox administration. The eyes of Dox-induced KR/TGF-α mice looked normal and transparent 20 ; no dramatic phenotypes were observed. This inconsistent consequence of ectopic expression of TGF-α in cornea of these two mouse strains is probably owing to different expression levels of TGF-α in their corneal stroma, which suggested that lower TGF-α level was produced in KR/TGF-α mouse strain.…”
Section: Discussionmentioning
confidence: 94%
“…This observation was unique and distinct from phenotypic changes found in other transgenic mouse lines that overexpress TGF-α and fibroblast growth factor-7 in eyelid stroma and corneal epithelial cells, respectively. 20,21 It has been reported that overexpression of EGF and/or EGFR caused apoptosis of cultured epithelial cells in vitro. 22,23 Thus, it is likely that excess TGF-α promoted corneal epithelial cell proliferation during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Meibomian gland morphogenesis commences at E18.5. The first sign of gland development is detected at the lid junction where the mesenchyme of neural crest and mesoderm origin underneath the future gland primordium starts to condense (Dong et al, 2015). The overlaying epithelial cells of ectoderm origin form the epithelium placode.…”
Section: Eyelid and Meibomian Gland Morphogenesis In Mousementioning
confidence: 99%
“…As a mitogen, TGFα can stimulate the proliferation of eyelid mesenchymal cells. In KR/TGFα transgenic mice, excess TGFα secreted by keratocytes stimulates hyper proliferation of eyelid tenocytes in eyelid tendon and tarsal plate (Dong et al, 2015). Reneker, et al, using αA-crystallin-TGFα transgenic mouse showed that as early as E15, TGFα could act as a chemoattractant to induce periocular mesenchymal cell migration towards the lens from both an anterior and posterior direction (Reneker, Silversides, Patel, & Overbeek, 1995).…”
Section: Egfr Signaling In Eyelid Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation